Development of the Cuzco region : the tourism contribution - Llorca Rodriguez, Carmen Maria; University of Granada (2012)
The objectives of this paper are, firstly, to measure the contribution of tourism to the economic growth of the Cuzco region (Peru) using the Ivanov and Webster methodology; and, secondly, to propose actions to turn the sector into its sustainable development trigger. Our results show a significant impact of this sector on the region’s economic growth and the relevance of community tourism to manage the natural, cultural and archaeological resources of this rural area characterised by a high level of poverty and serious infrastructures shortages and environmental restrictions. The potential negative effects of tourism could be avoided and the entire society could be profited by modifying the tourism development model with the cooperation of the local population